Binder Effects in SiO(2)‐ and Al(2)O(3)‐Bound Zeolite ZSM‐5‐Based Extrudates as Studied by Microspectroscopy - Whiting, Gareth T. (ChemCatChem, 2015)
Microspectroscopic methods were explored to investigate binder effects occurring in ZSM‐5‐containing SiO(2)‐ and Al(2)O(3)‐bound millimetre‐sized extrudates. Using thiophene as a selective probe for Brønsted acidity, coupled with time‐resolved in situ UV/Vis and confocal fluorescence microspectroscopy, variations in reactivity and selectivity between the two distinct binder types were established. It was found that aluminium migration occurs in ZSM‐5‐containing Al(2)O(3)‐bound extrudates, forming additional Brønsted acid sites. These sites strongly influence the oligomer selectivity, favouring the formation of thiol‐like species (i.e., ring‐opened species) in contrast to higher oligomers, predominantly formed on SiO(2)‐bound ZSM‐5‐containing extrudates. Not only were the location and distribution of these oligomers visualised by 3 D analysis, it was also observed that more conjugated species appeared to grow off the surface of the zeolite ZSM‐5 crystals (containing less conjugated species) into the surrounding binder material. Furthermore, a higher binder content resulted in an increasing overall reactivity owing to the greater number of stored thiophene monomers available per Brønsted acid site.